Pengaruh Sosial Media Instagram Marketing Terhadap Brand Image Consina Pada Saat Pandemi Covid-19 (Studi Kasus Mahasiswa Pecinta Alam DIY) The Influence Of Social Media Instagram Marketing On Consina’s Brand Image During The Covid-19 Pandemic (Case Stu - Florianus Pruda Muda; Endah Marendah Ratnaningtyas; Salamudin Salamudin (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2022)
Abstract: This study aims to analyze the influence of Social Media Instagram Marketing on Consina's Brand Image during the Covid-19 Pandemic. The population in this study were all student nature lovers in the Special Region of Yogyakarta with a sample of 100 respondents. The data processing method uses simple regression analysis. The data used are sourced from Nature Lovers Students in the Special Region of Yogyakarta who use Consina products by using a questionnaire distribution method to respondents. The results of this study indicate that sosial media Instagram marketing has a significant effect on brand image by 0.000 <0.05.